GAS THRUST BEARING OF INCREASED BEARING CAPACITY WITH YIELDING BEARING SURFACE - Kamil S. AKHVERDIYEV; Murman A. MUKUTADZE; Vladimir A. KONSTANTINOV (Advanced Engineering Research)
Basic operation factors of the deformed gas-lubricated thrust bearing with increased bearing capacity are theoretically analysed. It is shown that steady-state operation characteristics of this bearing differ from those of the rigid bearing.